Graph regularized low-rank representation for semi-supervised learning. (May 2021) - You, Cong-Zhe; Shu, Zhen-Qiu; Fan, Hong-Hui; Wu, Xiao-Jun
Low-rank representation (LRR) has attracted wide attention of researchers in recent years due to its excellent performance in the exploration of high-dimensional subspace structures. However, in the existing semi-supervised learning problem based on the LRR method, graph construction and semi-supervised learning are two separate steps. Therefore, the existing label information in the data set is not well used to guide the construction of the affinity graph. Therefore, these methods do not guarantee that the final result is a global optimal solution. This paper proposes a graph regularized low-rank representation for semi-supervised learning, called GLR2S2. This method combines the construction of affinity graph with semi supervised learning and unifies them into an optimization framework. By solving the joint optimization problem, the global optimal solution can be obtained. Experimental results on several standard data sets show that the GLR2S2 method proposed in this paper is effective.